An Analysis of Women’s Behaviours Stereotypes in ITZY Title Tracks: K-Pop Girl Group Song - Zaniar, Savira (Interdisciplinary Social Studies, 2022)
The Hallyu wave phenomenon becomes a trendsetter in Indonesia lately. Since K-Pop is starting to know spread Hallyu widely, K-Pop music has become a global trend nowadays in the music industry. This study tries to raise awareness of hidden difficulties in a song that we frequently listen to in our daily lives. It also aspires to provide a fresh viewpoint on how gender stereotypes are formed. This research used qualitative methods. Music videos (MVs) and lyrics from all of ITZY's title track songs serve as the study's key data. The information was gathered using the earlier in this section keyword ITZY songs on YouTube. Two theories were used to analyze the data. The first framework is based on Evans and Davies' gender stereotype theory, which consists of eight gender feminine characteristics. Copenhaver's idea of stereotyped gender features provides the second framework. First, the stereotype has been subverted by feminine characteristics that are only seen in passiveness qualities. Women have to express their aspirations and thoughts, and in "Mafia: In the Morning," they show their fierceness and savagery to be careful with women who intend to look as society standard (innocent, calm, and elegant) can be a danger or unbelievable, but this phenomenon cannot be generalized at all. Second, three behavioral qualities have been used to defy the stereotype: lack of confidence, fearfulness, and being people-oriented.